OM, NOM, NOM, This is Deeee-Licious!: An Overview of Nutrition for Kids. Issue 4 (2nd October 2021) - Phillips, Kat
Abstract: Childhood nutrition is a topic that will forever be at the forefront of the minds of families, caretakers, public policy makers, and children themselves. As the cost of health food options continues to create barriers, it is important to provide and maintain credible, and easy to access pools of information to aid in combatting this issue. Trusted consumer health websites such as MyPlate.gov, EatRight for Kids, Medline Plus's Child Nutrition, and Nutrition.gov's Nutrition by Age, are wonderful sources of information, videos, educational materials, and links to other external sources, but Instagram accounts like Kids.Eat.In.Color and FeedingLittles, and podcasts like Mystery Recipes and Maintenance Phase should be looped into the conversation as social and other media platforms are popular sources of information today.